Reviewing the epigenetics of schizophrenia - Cromby, John; Chung, Emma; Papadopoulos, Dimitris; Talbot, Chris (Taylor & Francis, 2016)
Background: Epigenetic research in mental health has grown exponentially during the last decade and holds what some claim are “revolutionary” potentials for the development of new interdisciplinary models of mental ill health. Schizophrenia is the most appropriate diagnosis against which to assess progress in this regard. Method: Papers on epigenetics and schizophrenia identified in a systematic literature search are subject to a conceptually-driven narrative review that assesses the relations between schizophrenia and epigenetics; considers some issues associated with empirical studies; and thereby identifies key assumptions guiding this research. Findings: The revolutionary potentials of epigenetics are thus far not being realised due to various influences, including a preponderance of hypotheses that begin from a primarily biological question; the “condensation” of environmental influences and their effective reduction to their molecular consequences; and a frequent reliance upon animal studies that effectively preclude some important influences already established as relevant to this diagnosis. Conclusion: Epigenetic research in schizophrenia (and mental health generally) could benefit from being more thoroughly interdisciplinary, from testing hypotheses that foreground social as well as biological influences, and from reconsidering its reliance upon psychiatric diagnoses.